1997
DOI: 10.1002/mrm.1910370223
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of and correction for artifacts in linogram MRI

Abstract: Chemical shift differences, field inhomogeneity, and gradient nonlinearity result in artifacts in magnetic resonance imaging. Three artifacts are characterized for linogram imaging and it is shown that, based on computer simulations and theory, linogram MRI behaves similarly to 2DFT. A correction technique similar to a scheme for 2DFT imaging based on the Dixon technique and coordinate transform methods is proposed. The algorithm is applied to correct for field inhomogeneity and gradient nonlinearity-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The oblique slice angle effect in both the regular and VAT sequences cannot be applied to the projection reconstruction because the readout direction is rotated by 1808 (3,25,26). The projection reconstruction has been widely used in routine MR imaging because of its intrinsic immunity to the motion and flow artifacts as first reported by Jung and Cho (12,27).…”
Section: Discussionmentioning
confidence: 99%
“…The oblique slice angle effect in both the regular and VAT sequences cannot be applied to the projection reconstruction because the readout direction is rotated by 1808 (3,25,26). The projection reconstruction has been widely used in routine MR imaging because of its intrinsic immunity to the motion and flow artifacts as first reported by Jung and Cho (12,27).…”
Section: Discussionmentioning
confidence: 99%
“…1 in the above equation corresponds to the projection data, gr(u, v), and Eq. [7] represents the one-dimensional Fourier transform of projection data (see Fig. 1) along u.…”
Section: R -1mentioning
confidence: 99%
“…In the discussion below, we assume that 2 N readout points and N total views are acquired for reconstruction on a N X N grid. Note that the additional factor of 2 is due to the different sampling requirements of the linogram geometry in comparison with the two-dimensional I T geometry (9). The number of views ac- ure 4.…”
Section: Lvzethodsmentioning
confidence: 99%
“…Our earlier work on linogram imaging has shown that this method offers similar motion robustness to projection reconstruction-based imaging (8). Additionally, standard linogram imaging behaves similarly to two-dimensional Fourier transform (FT) techniques in the presence of chemical shift and field inhomogeneity (9). The resulting geometric distortion and amplitude modulation can be corrected for accurately and in a computationally inexpensive manner when compared with projection reconstruction (PR) imaging, in which spatially varying blurring is dimcult to correct for.…”
mentioning
confidence: 99%